Development of powtoon learning media and literacy skills among elementary school students - Irnanda, Ela; Marlina (Universitas Jambi, Indonesia, 2025)
This research aims to develop Powtoon-based learning media to enhance literacy in grade IV elementary students. This research used research and development with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. This research employed several data collection techniques such as observation, interviews, documentation, and questionnaires. Additionally, the results indicate that the Powtoon-based media is valid, feasible, and practical, significantly improving student motivation. In addition, this medium can be used by teachers in the learning process applied to students, especially at the elementary school level. This Powtoon-based learning media gets very practical results. material understanding, and literacy skills. Positive student responses further support its application. Furthermore, this research recommends Powtoon-based media as an innovative solution for literacy learning in elementary schools.